A STUDY ON KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS SAFE MALE CIRCUMCISION AMONG YOUTH RECEIVING MEDICAL SERVICES AT LUGASA HEALTH CENTRE III, KAYUNGA DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Econi , Jonathan (Student's Journal of Health Research Africa, 2023)
Background: Objective: To determine youth’s knowledge about safe male circumcision as well as assess their attitude towards utilization of safe male circumcision services and also determine the practices in utilization of safe male circumcision at Lugasa Health Centre III. Methodology: The study was a descriptive cross-sectional study involving 88 respondents who were young males aged 15-40 years at Lugasa HCIII in Kayunga District selected by simple random sampling technique and the data was collected by the use of self-administered questionnaires after informed consent of the respondents. Data was entered in MS Excel and analyzed, and descriptive statistics such as frequency and percentages were used to present data on figures, charts, and tables. Findings: The majority of the respondents (97.5%) had never heard about SMC and had obtained information from the VHTs (41.25%). Promoting penile hygiene was the most popular (65%) reason for SMC, over half (52.5%) informed that SMC reduces the risk of HIV infection by 60%. The greatest number of respondents (95%) knew where SMC services can be accessed. The majority (74%) strongly agreed that circumcised males are liked by most women. Most of the respondents (58.75%) were circumcised, with 35% circumcised between 10-19 years of age. Health workers conducted the majority of the circumcision procedures (42.5%) and the majority of the circumcised males (35%) received paracetamol for pain management, and the least (16.25%) were screened for STIs. Conclusion: The respondents had good knowledge regarding safe male circumcision and equally had a positive attitude towards safe male circumcision which resulted in favorable practices of utilization of safe male circumcision. Recommendation: VHTs should be included to take part in the continuous medical education programs that are conducted regularly at Lugasa HCIII as they are most in contact with the community to spread updated information about safe male circumcision to society.